(untitled) (Journal of the College of Languages (JCL), 2022)
It is a common Knowledge that adverbs in Turkish languages can modify verbs, adjectives, nouns or other adverbs. Moreover, adverbs can determine the meanings of nouns and verbs in a sentence as far as time, place, manner, quantity and interrogative are concerned. The present study debates adverbs’ functions in Namiq Kamal’s play Vatan yahut Silistre. The study sheds light on the author’s use of the adverbs to describe the required theatrical actions of the play and to convey his reflections and thoughts easily to the auidence. One of the main hindrances encountered in conducting the study is the shortage of the upto date academic resources necessary for the study. Özet: Bilindiği gibi Türkçede zarfların fonkisyonu cümlede fiil ve isimlerin anlamını tamamlamaktır. Zarflar cümlede fiilin işlevi durum, zaman, yer-yön, miktar ve soru bakımndan açıklamaktadır. Araştırmalar neticesinde Namık Kemal’ın "Vatan Yahut Silistere" tiyatrosunda geçen zarflar üzerine bir çalışma yapılmadığı için, bu konu çalışmaya uygun görülmüştür. Dolayısıyla çalışmamızda zarfların tespiti üzerinde durulacaktır. Yazar tiyatroda cereyan eden olayları anlatmak, okuyucuyu etkilemek, fikirlerini açık ve basit bir şekilde aktarmak ve cümlelerin anlamlarını tamamlamak için, farklı farklı zarflar kullanmıştır. Çalışmada karşılaştığım sorunlardan biri de konuyla ilgili yeni kaynakların bulunmamasıdır.